Development of schemes of pump and gasoline-pump absorption water-ammonia refrigeration machines to work in a system of water production from the air - Осадчук, Евгений Александрович; Титлов, Александр Сергеевич; Кузаконь, Виктор Михайлович; Шлапак, Галина Всеволодовна (Technology audit and production reserves, 2015)
Perspectives of use of different types of refrigeration units for operation in systems for receiving water from the air in the absence of electrical power sources are analyzed. Such situation with a deficit of water and electric energy is typical for countries in Africa, Southeast Asia, South America. Prospects for use heat absorption water-ammonia refrigeration machines in such systems are analyzed. Solar collector with water as coolant is considered as heat source for the absorption refrigerating units. It is developed an original technique of calculation of the thermodynamic parameters of water-ammonia absorption cycle of refrigeration units, which allows you to determine the energy-efficient modes of operation and the relationship between the temperature of the object cooling, outside air and a source of thermal energy. Modes with maximum energy efficiency in the practical temperature range of the cooling medium (from 20 to 45 °C) and cooling facilities (from -30 to 15 °C) are shown during traditional AWARM cycle, and to achieve such optimum modes it is necessary the combination of the strong WA and temperature of the heating source. It is proposed the AWARM scheme with biasing booster compressor and scheme of pumpless AWARM. Researches are useful for developers of systems of receiving water from the air, particularly in tropical climates and in the absence of electrical power sources, as well as for developers of air conditioning systems. Developed water-ammonia systems at low outdoor temperature (in spring and autumn) can be used as a cooler of food and raw materials.